Routine follow-up may not be needed for people undergoing joint replacement surgery - Helen Saul; Samantha Cassidy; Brendan Deeney; Jemma Kwint; Philip Conaghan (BMJ, 2023)
The study Kingsbury SR, Smith LK, Czoski Murray CJ, et al. Safety of disinvestment in mid- to late-term follow-up post primary hip and knee replacement: the UK SAFE evidence synthesis and recommendations. Health Soc Care Deliv Res 2022;10. doi: 10.3310/KODQ0769 . To read the full NIHR Alert, go to: https://evidence.nihr.ac.uk/alert/joint-replacement-many-people-can-safely-wait-10-years-for-follow-up/